2020
DOI: 10.5194/soil-2020-9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Obtaining more benefits from crop residues as soil amendments by application as chemically heterogeneous mixtures

Abstract: Abstract. Crop residues are valuable soil amendments in terms of the carbon and other nutrients they contain, but incorporation of residues does not always translate into increases in nutrient availability, soil organic matter (SOM), soil structure, and overall soil fertility. Studies have demonstrated accelerated decomposition rates of chemically heterogeneous litter mixtures, compared to the decomposition of individual litters, in forest and grassland systems. Mixing high C : N ratio with low C : N ratio ame… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Soil is prone to degradation or decline in its quality due to misuse by the agricultural industry, such as a monoculture of crops, over application of chemical fertilizers, and pesticides and/or herbicides. In addition, soil is contaminated by anthropogenic activities, such as mineral resource exploiting and smelting, metal electroplating, paint and coating processing, and electronic equipment manufacturing [3][4][5]. Many studies have reported that crop residue incorporation has benefits on the improvement of soil quality and remediation of soil contamination [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Soil is prone to degradation or decline in its quality due to misuse by the agricultural industry, such as a monoculture of crops, over application of chemical fertilizers, and pesticides and/or herbicides. In addition, soil is contaminated by anthropogenic activities, such as mineral resource exploiting and smelting, metal electroplating, paint and coating processing, and electronic equipment manufacturing [3][4][5]. Many studies have reported that crop residue incorporation has benefits on the improvement of soil quality and remediation of soil contamination [6][7][8].…”
Section: Introductionmentioning
confidence: 99%